Creation and promoting frameworks of cultivated tilapia in China - Donnie Tsung; Jiang Laozi; Qing Lee (Advances in Aquaculture and Fisheries Management, 2018)
Tilapia has become one of the major species of aquatic products in close link with both domestic and international markets. Nowadays, the demand for fish and fisheries product has being exacerbated by the continued increase in human population the world over. This was due to the fact that global captured fishery was declining following the increased human exploitation for the commercially important fishes. Aquaculture or fish farming has become one of the solutions to maintaining the continuous supply of fish to commercial markets. China was by far the largest producer and exporter of tilapia products irrespective of some constraints such as soaring production costs, price and weather fluctuations. In the country, tilapia production was mostly carried out in the southern and southeastern coastal areas where subtropical conditions favored the growth and reproduction of the species. This paper reports on production and marketing systems of tilapia in China. Tilapia products produced in China had to pass through different channels before reaching their final consumers. Major international markets for tilapia products produced in China included among others, the United State, European Union and Russia. This work will guide potential investors and competitors for tilapia market in China and the world at large